From Synthesis to Clinical Trial: Novel Bioinductive Calcium Deficient HA/β-TCP Bone Grafting Nanomaterial - Mishchenko, O. M.; Yanovska, A.; Sulaieva, O.; Moskalenko, R.; Pernakov, M.; Husak, Ye.; Korniienko, V.; Deineka, V.; Kosinov, O. S.; Varakuta, O. A.; Ramanavicius, S.; Varzhapetjan, S. D.; et al. (My University, 2023)
Maxillary sinus augmentation is a commonly used procedure for the placement of dental implants. However, the use of natural and synthetic materials in this procedure has resulted in postoperative complications ranging from 12% to 38%. To address this issue, we developed a novel calcium deficient HA/ -TCP bone grafting nanomaterial using a two-step synthesis method with appropriate structural and chemical parameters for sinus lifting applications. We demonstrated that our nanomaterial exhibits high biocompatibility, enhances cell proliferation, and stimulates collagen expression. Furthermore, the degradation of -TCP in our nanomaterial promotes blood clot formation, which supports cell aggregation and new bone growth. In a clinical trial involving eight cases, we observed the formation of compact bone tissue 8 months after the operation, allowing for the successful installation of dental implants without any early postoperative complications. Our results suggest that our novel bone grafting nanomaterial has the potential to improve the success rate of maxillary sinus augmentation procedures.
Keywords: bone grafting nanomaterials; bionanotechnology; maxillary sinus lifting; synthetic bone materials; HA/ -TCP; bionanomaterials; scaffolds; clinical cases; dental implants; nanostructures